2022
DOI: 10.1177/11782234221086992
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Treatment of HER2-Positive Metastatic Breast Cancer With Dual Blockade Including Biosimilar Trastuzumab (SB3): Population-Based Real-World Data From the DBCG

Abstract: Purpose: Dual blockade with trastuzumab and pertuzumab in combination with chemotherapy is the recommended first-line therapy for human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer (mBC). The purpose of this retrospective study is to examine the clinical outcomes of the trastuzumab biosimilar SB3 in first-line dual blockade treatment using real-world data of patients with HER-positive mBC. Methods: In Denmark, all women with breast cancer are registered in the database of the Dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
5
1
Order By: Relevance
“…Patients with HER2-positive, HR-positive breast cancer also prevailed in other studies, but the percentage of those patients was lower (47-70%), which could translate into a higher ORR. A significant percentage of patients in our study had previously received systemic therapy for early breast cancer (55.7%), while in other studies, except for the Chinese study [28] and the SB3 evaluation study [29], this group of patients usually did not exceed 50% (27.8%-48%). These differences in the structure of the patient group also could potentially translate into slightly poorer therapy outcomes, as well as potentially higher rates of cardiotoxic complications.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Patients with HER2-positive, HR-positive breast cancer also prevailed in other studies, but the percentage of those patients was lower (47-70%), which could translate into a higher ORR. A significant percentage of patients in our study had previously received systemic therapy for early breast cancer (55.7%), while in other studies, except for the Chinese study [28] and the SB3 evaluation study [29], this group of patients usually did not exceed 50% (27.8%-48%). These differences in the structure of the patient group also could potentially translate into slightly poorer therapy outcomes, as well as potentially higher rates of cardiotoxic complications.…”
Section: Discussioncontrasting
confidence: 51%
“…The median PFS achieved in these studies ranged between 14.5 and 27.8 months [24][25][26][27][28]. Equivalent results were also presented in a study evaluating a trastuzumab biosimilar (SB3); the mPFS obtained in this study was 12.7 months [29]. Table 5 shows a comparison of the results of the most frequently quoted studies evaluating the efficacy and safety of PTH therapy.…”
Section: Discussionmentioning
confidence: 54%
“…Conversely, survival remained substantially unchanged for patients with triple-negative or HR+/HER2-negative MBC [ 63 ]. Similarly, population-based studies from Canada, Denmark, Sweden and Australia showed that median OS, for patients receiving double anti-HER2 blockade, rose from 21.8 during 2006–2014 to 39.2 months during 2012–2017, compared to 14 months for patients diagnosed during 1985–2000 who did not receive trastuzumab [ 64 67 ].…”
Section: New Treatmentsmentioning
confidence: 99%
“…Dual HER-2 blockade has become the accepted neoadjuvant approach for HER2-positive breast cancer 10,11 . However, there are still incidences of drug resistance following therapy 12 .…”
Section: Paclitaxelmentioning
confidence: 99%